2018
DOI: 10.1111/ejss.12530
|View full text |Cite
|
Sign up to set email alerts
|

Larger Q10 of carbon decomposition in finer soil particles does not bring long‐lasting dependence of Q10 on soil texture

Abstract: Summary Soil particle‐size fractionation is a reliable approach for the separation of carbon (C) pools with different stabilities. Our previous study found that C decomposition in fine soil particles had greater temperature sensitivity (Q10) than in coarse particles in grassland and forest soils. However, it is not known whether this phenomenon occurs in cropland soil and whether it generally suggests a dependence of Q10 on soil texture. We carried out a 107‐day incubation of isolated soil particles from cropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…This trend was also observed in a forest and a grassland soil (Ding et al, 2014) and two cropland soils including upland and paddy (Ding et al, 2018). An analysis based on 9415 data points of European forest and grassland soils reported that the C/N ratio of MAOM (13 ± 5) was lower and less variable than that of POM (22 ± 15) (Cotrufo et al, 2019).…”
Section: Discussionsupporting
confidence: 59%
“…This trend was also observed in a forest and a grassland soil (Ding et al, 2014) and two cropland soils including upland and paddy (Ding et al, 2018). An analysis based on 9415 data points of European forest and grassland soils reported that the C/N ratio of MAOM (13 ± 5) was lower and less variable than that of POM (22 ± 15) (Cotrufo et al, 2019).…”
Section: Discussionsupporting
confidence: 59%
“…7). Soil contains differently sized mineral particles, which are usually classi ed simply as sand, silt and clay (Ding et al 2018). We found clay content has negative relationship with RR of soil fractions.…”
Section: Driving Factors On Response Ratiomentioning
confidence: 71%
“…2.2 Soil respiration rate (R s ) and Q 10 Fifty grams of fresh soil was placed into a 500-ml butyl lithium bottle and incubated at six temperature gradients: 5°C, 10°C, 15°C, 20°C, 25°C and 30°C, to systematically measure the CO 2 emission rate of each treatment and their sensitivity to temperature changes. According to the previously described incubation method (Lefèvre et al, 2014;Ding et al, 2017), the fresh samples were preincubated with lids open at 20°C for 7 days to stabilize microbial activities. Once the formal experiment started, 50 grams of incubated soil was placed into a butyl lithium bottle, accompanied by a plastic bottle containing 20 ml of 0.1 M NaOH solution to absorb the released CO 2 , with three replicates.…”
Section: Experimental Design and Soil Samplingmentioning
confidence: 99%